Buttons on Demand Sliding Mechanism Driven by Smart Materials and Mechanical Design - Christianto Renata; Manivannan Sivaperuman Kalairaj; Hong Mei Chen; Gih Keong Lau; Wei Min Huang (Actuators, 2021)
In this paper, we describe a novel human interaction platform in a car, called buttons on demand, that will serve as buttons inside the interior of a car, which can be called upon and activated when required but remain concealed and inactive when not required. The mechanism to obtain such interaction is driven by a combination of smart materials and mechanical design. The elaboration of smart materials and mechanical design employed to achieve this mechanism is discussed. A demonstration of how the buttons on demand mechanism described in this paper can potentially substitute or minimize the use of bulkier physical buttons in cars and provide the user with haptic and tactile feedback with low power consumption and fast response time is also presented.